Agribusiness in small farm development : crop production under tripartite contract among farmers' group, "anchor firm" and the land bank of the Philippines in an agrarian reform area of Bukidnon - Quiblat, Hubert Berro; Weber, Karl E.; Dias, Hiran D.; Demaine, Harvey; Gonzales, Jr. R. L.; The Canadian International Development Agency - Broad Based Development Program (CIDA-BBDP) (Bangkok : Asian Institute of Technology, 1986)
The major objective of this study is to determine socio-economic phenomena resulting from the implementation of the "Anchor Firm Tie-up Scheme", a program of the Land Bank of the Philippines designed to assist agrarian reform beneficiaries to raise land and labor productivity, thereby increasing income. This study, of the impact of the tobacco project implemented in Bukidnon, compares three groups of respondents, namely: the tobacco project participants, the non-participants holding land and the landless non-participants . The findings show that the tobacco project had significantly increased the earnings of the project participants , in terms of farm productivity per hectare and earning per unit of labor force. Despite this economic gain, the project participants and, much more , both groups of non-participants did not fully appreciate the tobacco project. Recommendations to facilitate more favorable impact and to create a better working atmosphere in the tobacco project include the improvement of the quality of tobacco produced, the redesign of the fire-prone flue-curing barns, the training of farmers in the grading of cured tobacco leaves, the cultivation of fast growing trees in barren lands for firewood production, and the extension of institutional credit to all households located in a given area, irrespective of immediate and direct involvement in a specific project.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1986
Keywords: Land reform -- Philippines; Agriculture -- Economic aspects -- Philippines